Society Perception of Pasung Behavior in People with Mental Disorders - Nur Khriesna Habita1, Ahmad.Yusuf2, Rr Dian Tristiana2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Pasung intervention of people with mental disorder still happened in the society. “Pasung Free Program” which has already designed in Indonesia since 2014 did not effective to wipe out Pasung behavior. There are still many people who are abused by Pasung behavior in Kulon Progo, Java Island, Indonesia with the various perception of society. The aims of this study examined the public perception of Pasung behavior in people with mental disorders. Method: This study used quantitative method by using symbolism interaction approach. There were 9 people who experienced pasung in their surroundings that became samples. Data was collected by using in-depth interviewing and socio-demographic questionnaire. Method that was used to analyze was analysis method such as 6 stages of Creswell analysis that was suitable with the used method. Result: The result of this study could become a theme. There were 8 themes came from two different perceptions. Perception of society resulted two themes namely 1) opinion about pasung behavior and 2) conclusion about pasung. External perception resulted six themes namely 1) the reason why pasung is allowed, 2) the reason why pasung is not acceptable, 3) pemasungan idea, 4) pemasungan method, 5) the society’s hope about people with mental disorder, and 6) the obstacle of health service. Conclusion: Society perception about mental disorder still not acceptable. Pasung program planning should be in line with free people with mental disorders program. The appearance of pasung behavior related to the increase of people with mental disorders.